Simulation study of automatic voltage regulator system by using PID and MRAC controller - Ang, Chun Jin; R., Hamdan; Jalil, M. H. A. (Penerbit UTHM, 2020)
The applications of Automatic Voltage Regulator (AVR) had been widely used in past decades. Precise and fast responsive controller is needed for AVR because most of the electrical equipment are sensitive to the voltage level. Majority of the devices that connected to the grid have its own desired voltage level, or so-called nameplated value for proper functioning. The problem arises when the voltage level fluctuates or beyond the operation limit of electrical equipment, it will affect the performance and case comes to the worst, the equipment will be damaged seriously [1]. Therefore, the demand of having precise controller is increasing lately...